Letter-By-Letter Reading: Natural Recovery and Response to Treatment - Pélagie M. Beeson; Joël G. Magloire; Randall R. Robey (Behavioural Neurology)
The present investigation provides a longitudinal study of an individual (RB) with acquired alexia following left posterior cerebral artery stroke. At initial testing, RB exhibited acquired alexia characterized by letter-by-letter (LBL) reading, mild anomic aphasia, and acquired agraphia. Repeated measures of reading accuracy and rate were collected for single words and text over the course of one year, along with probes of naming and spelling abilities. Improvements associated with natural recovery (i.e., without treatment) were documented up to the fourth month post onset, when text reading appeared to be relatively stable. Multiple oral reading (MOR) treatment was initiated at 22 weeks post-stroke, and additional improvements in reading rate and accuracy for text were documented that were greater than those expected on the basis of spontaneous recovery alone. Over the course of one year, reading reaction times for single words improved, and the word-length effect that is the hallmark of LBL reading diminished. RB's response to treatment supports the therapeutic value of MOR treatment to in LBL readers. His residual impairment of reading and spelling one-year post stroke raised the question as to whether further progress was impeded by degraded orthographic knowledge.